2012
DOI: 10.12697/poa.2012.21.08
|View full text |Cite
|
Sign up to set email alerts
|

Finger and palmar dermatoglyphics in Muzeina Bedouin from South Sinai: A quantitative study

Abstract: Quantitative finger and palmar dermatoglyphics of 218 individuals (170 males and 48 females) belonging to the Muzeina Bedouins from South Sinai Peninsula. They are characterized with a high degree of consanguinity, a small isolate nomadic tribe. 22 quantitative dermatoglyphic traits (12 finger and 10 palms) were considered in the present study. Except PII (non-significant sex difference), the results of significant sex-differences of finger ridge counts (TFRC), MLI are similar with the earlier studies in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
6
2
Order By: Relevance
“…The core results of our study are in partial accordance with the studies conducted by various other researchers 4,[6][7][8]10,[15][16][17][19][20][21][22][23] who also found loop pattern to be most common in the various populations studied by them (as shown in Table 3). Also, the results of our study are found to be in contrast to the studies conducted by some researchers 9,[11][12][13][14]18 who reported whorls to be the most common pattern, followed by loops and arches in both the hands of male and females.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The core results of our study are in partial accordance with the studies conducted by various other researchers 4,[6][7][8]10,[15][16][17][19][20][21][22][23] who also found loop pattern to be most common in the various populations studied by them (as shown in Table 3). Also, the results of our study are found to be in contrast to the studies conducted by some researchers 9,[11][12][13][14]18 who reported whorls to be the most common pattern, followed by loops and arches in both the hands of male and females.…”
Section: Resultscontrasting
confidence: 99%
“…In the past, attempts have been made by researchers to study the distribution of fingerprint patterns in various populations and ethnic groups. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The present study was aimed to determine the detailed frequency distribution of various fingerprint patterns, establish the most and least predominant patterns and to find out existence of any statistically significant gender differences in the Central Indian Muslim population.…”
Section: Introductionmentioning
confidence: 99%
“…The PII index, together with other descriptive features, or more often with quantitative characteristics, is taken into account in population research, e.g., Harich et al (2002), Karmakar et al (2002aKarmakar et al ( , 2008a, ,b, 2012, 2013a, Kavgazova et al (1999), Kobyliansky and Micle (1987), Martín et al (1996), Kobyliansky (1985, 1986), Morelli et al (1999), Pons (1990), Scheil et al (2005), Sengupta and Karmakar (2003), Siváková and Pospíšil (2001), Sokal and Livshits (1993), clinical research, e.g., Bejerano et al (2001), Floris and Marini (1998), Kobyliansky et al (1997Kobyliansky et al ( , 1999aKobyliansky et al ( ,b, 2004b, Kobyliansky et al, 2005), as well as in intercorrelation research, e.g., Loesch (1986), research on the asymmetry of dermatoglyphs, e.g., Buchwald (2002), Karmakar et al (2001Karmakar et al ( , 2005a, Micle and Kobyliansky (1991).…”
Section: Categories Of Parentsmentioning
confidence: 99%
“…Similarly, the study on Muzziena Bedouin in South Sinai by Karmakar et al . [ 15 ] observed that loop was the most common pattern in males followed by whorls and arch, whereas whorl pattern was found more frequently in females followed by loops and arch. Namouchi [ 16 ], in her study on Tunisians of Tunisia observed that loop was the most common pattern followed by whorl and arch in both males and females, which was similar to the study by Qazi et al .…”
Section: Introductionmentioning
confidence: 99%